Application of motor learning and neuroscience knowledge in basketball training: case report of an under-13 winner team of the Brazilian and Sulamerican championships (Research, Society and Development, 2022)
This case report shows how scientific knowledge produced in Motor Learning and Neuroscience areas were applied in the training of an under-13 basketball team. The performance of five athletes was analyzed in two competitions in which the team won, the Sulamerican and Brazilian championships of the 2017 season. In the present study, less repetitive practice, control over activity length and reduced extrinsic feedback were incorporated into the daily training of the basketball athletes in order to promote better motor learning, as described by studies in the Motor Learning field. The results suggested that the training geared towards factors that contribute to processes related to slow learning during a period of eleven months was enough to bring about positive changes in collective and individual performances. In addition to improved performance, a change in tactical behavior was observed through the decentralization of moves inside the key, an aspect that reflects the better use of the offense zone. The adaptation of the theoretical knowledge to the training seems to impacts positively in the performance of the athletes in all variables evaluated.